Analisis Pembelajaran Pendidikan Jasmani Olahraga dan Kesehatan Melalui Permainan Tradisional dalam Menginternalisasikan Nilai Karakter Pada Siswa Sekolah Dasar - Sutarman Sutarman; Hendra Saputra (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to analyze Physical Education, Sports, and Health (PJOK) learning through traditional games as a medium for integrating character values among elementary school students. The background of this research is rooted in the dominance of physical-oriented PJOK learning, the limited utilization of local wisdom as instructional media, and the insufficient understanding among teachers regarding the importance of character education in PJOK. This study employs a descriptive qualitative approach, with data collected through interviews, observations, and document analysis. The research was conducted at SD Negeri Jamur Labu, Aceh Tamiang, involving 25 fifth-grade students and three key informants consisting of the school principal, the PJOK teacher, and the fifth-grade homeroom teacher. Data were analyzed using NVivo software to identify themes related to planning, implementation, and learning impact. The findings indicate that PJOK learning that incorporates traditional games is systematically planned and directed toward character development. Teachers select age-appropriate, safe, simple, and meaningful traditional games that promote honesty, cooperation, discipline, and sportsmanship. During the implementation phase, teachers act as facilitators who guide students to practice character values, mediate conflicts, reinforce discipline, appreciate positive behavior, and conduct reflective learning through storytelling activities. Furthermore, the study reveals that traditional games significantly contribute to character development, as shown by improvements in students’ honesty, discipline, confidence, cooperation, respect toward peers, and comfort in social interaction. Despite challenges related to limited space, weather conditions, and shy students, teachers successfully adapt their strategies to achieve learning objectives.